BONE MINERAL DENSITY IN PHYSICALLY ACTIVE WOMEN ASSESSED BY ULTRASOUND DESINTOMETRY - Ana Marijanac; Milena Mikalački; Nebojša Čokorilo (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
Osteoporosis is a disease characterized by low bone mass and density. Physical activity has a positive effect on bone tissue, and it is recommended to prevent bone loss which comes with age. Methods: In purpose of determining bone mineral density in women who are physically active we examined 35 women divided into two groups - subjects who are premenopausal (n=20, 43.52 ± 7.56 years), and subjects who are postmenopausal (n=15, 55.89 ± 5.48). The subjects exercised Pilates method twice a week for one hour. Bone mineral density measurements were done by ultrasound densitometer "Sahara" through the calcaneus. We get the data of the estimated bone density and T-score for right and left foot separate. Results: According to results premenopausal women have normal bone density, and postmenopausal values represent osteopenia, according to the WHO. There is no subjects who established osteoporosis. Discussion: Previous investigations have confirmed that physical activity is important for the preservation of the bone quality. Increasing steps, using simple everyday tasks, can prevent decrease in BMD in postmenopausal women (Muir et al., 2013, Ashe et al, 2008). There's difference in the density of the calcaneus between physically active and those who are not, measured by ultrasound densitometry (Vainionpää et al, 2005). We use quantitative ultrasound densitometry to describe BMI of women who exercise Pilates and support the finding that physical activity is one of the ways that may prevent the BMD loss. These research was done as a part of long-term project entitled "Impact of physical activity of the working population" which is co-financed by Provincial Secretariat for Science and Technological Development.